INNOVATIVE TECHNIQUES FOR TEACHING GRAMMAR TO ADULT AND PART-TIME LEARNERS - Maxkamova Komila Toktamuratovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
Teaching grammar is a fundamental responsibility of language instructors, providing students with the tools to communicate effectively. Grammatical structures form a critical part of this linguistic toolkit. However, teaching grammar can sometimes feel monotonous or challenging, particularly after years of practice. To revitalize grammar lessons, adopting innovative strategies tailored for English language learners is essential.